Response of meat chickens to different sources of arginine in low‐protein diets. Issue 4 (7th January 2021) - Dao, Hiep T.; Sharma, Nishchal K.; Bradbury, Emma J.; Swick, Robert A.
Abstract: Arginine activity in broiler diets can be supplied by L‐arginine (Arg), guanidinoacetic acid (GAA) and L‐citrulline (Cit), all of which are commercially available. This study was conducted to assess the effects of Arg source and level on broiler performance, nutrient digestibility and carcass parameters. Day‐old Ross 308 cockerels ( n  = 768) were assigned to one of eight dietary treatments using a completely randomized design: normal protein (NP), low protein deficient in Arg (LP) and LP with two levels of either Arg (0.238% and 0.476%), GAA (0.309% and 0.618%) or Cit (0.238 and 0.476%). The LP was 5 percentage points lower in protein level than the NP. Wheat, sorghum, soya bean meal, canola meal, and meat and bone meal‐based diets were fed over three feeding phases to 6 replicate floor pens with 16 birds each. Compared to NP, birds fed LP had reduced feed intake (FI, p  < 0.001), reduced body weight gain (BWG, p  < 0.001) and increased feed conversion ratio (FCR, p  < 0.001) from day 0 to day 35. Additions of Arg or Cit to the LP at both levels resulted in increased BWG and reduced FCR ( p  < 0.05). Birds fed LP with GAA added had lower FCR ( p  < 0.05) but not higher BWG ( p  > 0.05) compared with the LP observed from day 0 to day 35. Supplementation of Arg, Cit and the low level of GAA to LP resulted in increased carcass yield, bone length, diameter and ash ( p  < 0.05) but did not increase ileal energy or nitrogen digestibility ( p  > 0.05). The findings indicate that Cit is an efficacious source of Arg activity in Arg‐deficient diets.